Sources and factors controlling the distribution of heavy metals in coastal sediments of Haiyang, China. (February 2022) - Hu, Rijun; Wang, Yang; Zhang, Xiaodong; Zhu, Longhai; Luo, Minyi; Liu, Bo; Yuan, Xiaodong
Abstract: In this study, the pollution level of heavy metals (HMs), their sources as well as factors influencing their distribution, were studied using data about the concentration of Cr, Pb, Cu, As, Hg and Zn in surface sediment samples from Haiyang coastal areas, and those on sediment grain size and tidal residual currents. Cr, Cu and Pb originated from natural processes and had similar distributions which were mainly affected by sediment grain size, tidal residual currents and coastal currents. Areas with high levels of these elements were also mainly located in the sedimentation zone of fine materials with weak hydrodynamic force. In contrast, Zn and Hg were derived from anthropogenic activities such as industrial sewage and raft cultures, while As originated from both natural and human sources. Overall, sediment grain size, hydrodynamic effects and human activities were the main factors affecting the distribution of HMs in the Haiyang coastal sea. Highlights: Cr, Cu and Pb mainly originate from natural sources, Zn and Hg mainly come from aquaculture; As comes from both sources. The distribution of heavy metals from natural sources is different from that from human activities. Sediment grain size, hydrodynamic and human activities are the factors controlling the distribution of heavy metals.